A non-expansive fire retardant coating for steel structure and preparation method thereof

By adopting fire-retardant coating preparation methods with modified sepiolite zeolite mixture and other components, the problem of poor performance of existing fire-retardant coatings in unfavorable environments is solved, and the fire resistance limit, water resistance, heat exposure resistance and smoke corrosion are achieved. The significant improvement and excellent thermal insulation performance.

CN119161759BActive Publication Date: 2025-02-07QUANZHOU LIANZHONG IND & TRADE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411630887.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-07
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Existing non-expanded steel structure fire-retardant coatings are prone to cracking in adverse environments, are intolerant of environmental influences, have poor water resistance and short fire resistance, making it difficult to meet the high performance requirements under complex working conditions.

Method used

Fire-retardant coatings are prepared by high-temperature sintering and ball milling, and the mixture of modified sepiolite zeolite, triisopropanolamine cycloborate, polyvinylpyrrolidone, water glass, pentaerythritol, melamine and ammonium polyphosphate. The dispersion treatment is carried out under ultrasonic conditions to form a fire-resistant coating with excellent performance.

Benefits of technology

The fire resistance limit is achieved for more than 315 minutes, water resistance and heat exposure resistance can reach more than 42 days and more than 1842 hours respectively, and can withstand more than 86 smoke corrosion treatments. It has excellent thermal insulation performance and significantly improves fire resistance coatings. performance level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention belongs to the technical field of fire retardant coatings. The present invention provides a non-expansive steel structure fire retardant coating and a preparation method thereof. The fire retardant coating comprises the following components by weight: 10 to 18 parts of a modified sepiolite zeolite mixture, 5 to 15 parts of triisopropanolamine cyclic borate, 3 to 5 parts of polyvinyl pyrrolidone, 5 to 8 parts of water glass, 5 to 8 parts of pentaerythritol, 3 to 5 parts of melamine, 10 to 15 parts of ammonium polyphosphate, and 60 to 80 parts of water. The fire retardant coating obtained by the present invention has excellent performance, a fire resistance limit of more than 315 minutes, water resistance and heat resistance can reach more than 42 days and more than 1842 hours respectively, and can withstand more than 86 smoke corrosion treatments; it can also have excellent thermal insulation performance under 1300°C flame spraying. The present invention solves the defects of existing fire retardant coatings that are not tolerant to adverse environments, have poor water resistance and a short fire resistance time, and has good industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fire retardant coatings, and in particular relates to a non-expansion type fire retardant coating for steel structures and a preparation method thereof. Background Art

[0002] Non-expansion steel structure fire retardant coatings use the material's own non-combustibility, low thermal conductivity or the heat absorption of the coating material to delay the temperature rise of steel in the fire and protect the steel. Non-expansion macro defects such as delamination, cracking, and peeling will develop into more serious defects if not handled in time.

[0003] At present, relevant technical standards, such as GB14907-2018 "Steel Structure Fire Retardant Coatings", have specific requirements for the performance of non-expanding steel structure fire retardant coatings. However, in actual industrial applications, due to the complex adverse environment (such as high humidity, heat exposure, smoke corrosion), steel structure fire retardant coatings will face more severe challenges. Therefore, in many application environments, people have higher requirements for the performance of steel structure fire retardant coatings.

[0004] Chinese patent ZL202211105230.5 provides an aerogel non-expanding steel structure fire retardant coating, the fire resistance limit time of which is higher than the 3-hour requirement of the aforementioned technical standard, reaching 270 minutes, and has excellent water resistance. Chinese patent ZL201811302481.6 provides a graphene-modified fire retardant coating with a maximum fire resistance time of 137 minutes and a water resistance of more than 72 hours, which also meets the requirements of the aforementioned industry standards.

[0005] However, in many working conditions, steel is sometimes immersed in water for a long time, or is subjected to adverse environmental influences far exceeding the above technical standards. Therefore, the field needs to develop fire retardant coatings with higher performance levels for these situations. However, the field has not yet found an effective research and development route or theory to follow, making research and development in this area more difficult. Summary of the invention

[0006] The purpose of the present invention is to provide a non-expanding steel structure fire retardant coating and a preparation method thereof in view of the defects of the fire retardant coating in the prior art, such as easy cracking, intolerance to adverse environment, easy water absorption and short fire resistance time.

[0007] In order to achieve the above object, the technical solution provided by the present invention is as follows:

[0008] A non-expandable fire retardant coating for steel structures, the fire retardant coating comprising the following components by weight: 10 to 18 parts of a modified sepiolite zeolite mixture, 5 to 15 parts of triisopropanolamine cyclic borate, 3 to 5 parts of polyvinyl pyrrolidone, 5 to 8 parts of water glass, 5 to 8 parts of pentaerythritol, 3 to 5 parts of melamine, 10 to 15 parts of ammonium polyphosphate, and 60 to 80 parts of water;

[0009] The modified sepiolite-zeolite mixture is prepared by mixing modified sepiolite and zeolite in a weight ratio of 5:1 and sintering at high temperature;

[0010] The preparation method of the modified sepiolite comprises: (1) soaking sepiolite in hydrochloric acid to obtain acid-treated sepiolite; (2) placing the acid-treated sepiolite, titanium dioxide and silicon dioxide in an ethanol aqueous solution in a weight ratio of 8:1:2, and fully mixing them under ultrasonic conditions to form a slurry; (3) adding the obtained slurry to an ethanol aqueous solution of γ-methacryloxypropyltrimethoxysilane, then adjusting the pH to 5, stirring and incubating at 60° C. for 5 hours, then filtering and washing with anhydrous ethanol, and then vacuum drying to obtain the modified sepiolite.

[0011] Furthermore, the acid-treated sepiolite is prepared by placing the sepiolite in a 5 mol / L hydrochloric acid aqueous solution at a solid-liquid ratio of 1 g:20 mL, treating the sepiolite at 60° C. for 18 hours, washing with distilled water and drying the sepiolite.

[0012] Furthermore, in step (2) of the method for preparing modified sepiolite, the ultrasonic conditions are: the ultrasonic frequency is 100 Hz and the treatment time is 2 hours.

[0013] Furthermore, in step (2) of the method for preparing modified sepiolite, the volume fraction of the ethanol aqueous solution is 80%, and the weight fraction of the γ-methacryloxypropyltrimethoxysilane after being dissolved in the ethanol aqueous solution is 3%.

[0014] Furthermore, when preparing the modified sepiolite-zeolite mixture, the modified sepiolite and zeolite are mixed in a weight ratio of 5:1, and then sintered in a muffle furnace at 600° C. for 2 hours.

[0015] Furthermore, the fire retardant coating comprises the following components by weight: 15 parts of a modified sepiolite zeolite mixture, 8 parts of triisopropanolamine cyclic borate, 4 parts of polyvinyl pyrrolidone, 6 parts of water glass, 6 parts of pentaerythritol, 4 parts of melamine, 12 parts of ammonium polyphosphate, and 75 parts of water.

[0016] Furthermore, the modified sepiolite zeolite mixture is also ball-milled to have a particle size distribution of 80-120 μm.

[0017] The preparation method of the above-mentioned non-expansion steel structure fire retardant coating comprises the following steps:

[0018] (1) Prepare raw materials according to the weight proportions of the raw materials in the above-mentioned non-expanding fire retardant coating for steel structures;

[0019] (2) dispersing the modified sepiolite zeolite mixture, pentaerythritol, melamine, and ammonium polyphosphate in water to prepare a slurry;

[0020] (3) adding triisopropanolamine cyclic borate, polyvinyl pyrrolidone and water glass to the obtained slurry for dispersion treatment to obtain the fire retardant coating.

[0021] Furthermore, in step (2), the dispersion is carried out under ultrasonic treatment, the ultrasonic frequency is 100 Hz, and the treatment time is 2 hours.

[0022] Furthermore, in step (3), the dispersion treatment is carried out under ultrasonic treatment, the ultrasonic frequency is 40 Hz, and the treatment time is 1 hour.

[0023] As shown in the results of the relevant experimental examples of the present invention, in the present invention, when the modified sepiolite and zeolite are used to prepare the modified sepiolite-zeolite mixture, it is very important to modify the sepiolite with titanium dioxide and silicon dioxide. When titanium dioxide or silicon dioxide is not added, the performance of the obtained fire-resistant coating will be greatly reduced. In addition, adding polyvinyl pyrrolidone on the basis of triisopropanolamine cyclic borate and water glass is also necessary for the performance of the obtained fire-resistant coating.

[0024] Beneficial effects of the present invention:

[0025] The non-expansive steel structure fire retardant coating obtained by the present invention has excellent performance, the fire resistance limit reaches more than 315 minutes, the water resistance and heat resistance can reach more than 42 days and more than 1842 hours respectively, and can withstand more than 86 smoke corrosion treatments. In addition, it can also have excellent thermal insulation performance under 1300°C flame spraying. The present invention solves the defects of existing fire retardant coatings that they are not strong in tolerance to adverse environments, have poor water resistance and short fire resistance time, and has good industrial application prospects. DETAILED DESCRIPTION

[0026] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technical personnel in this field based on the above invention content still fall within the scope of protection of the present invention.

[0027] Example 1

[0028] 1. Preparation of modified sepiolite:

[0029] (1) placing sepiolite in a 5 mol / L hydrochloric acid aqueous solution at a solid-liquid ratio of 1 g:20 mL, treating at 60° C. for 18 hours, washing with distilled water and drying to obtain acid-treated sepiolite;

[0030] (2) placing the acid-treated sepiolite, titanium dioxide and silicon dioxide in an ethanol aqueous solution with a volume fraction of 80% ethanol in a weight ratio of 8:1:2, and ultrasonically treating the solution for 2 hours at an ultrasonic frequency of 100 Hz to fully mix and uniformly form a slurry;

[0031] (3) Add an ethanol aqueous solution of γ-methacryloxypropyltrimethoxysilane (the weight fraction of γ-methacryloxypropyltrimethoxysilane in its ethanol aqueous solution is 3%) to the obtained slurry at a volume ratio of 1:3, then adjust the pH to 5, stir and incubate at 60° C. for 5 hours, then filter and wash with anhydrous ethanol, and then vacuum dry to obtain the product.

[0032] (II) Preparation of modified sepiolite zeolite mixture:

[0033] The modified sepiolite and zeolite obtained in step (i) were mixed in a weight ratio of 5:1, and then sintered in a muffle furnace at 600° C. for 2 hours, and then ball-milled to obtain a particle size distribution of 80-120 μm.

[0034] (III) Preparation of coating raw materials:

[0035] Prepare the following raw materials by weight: 15 parts of a modified sepiolite zeolite mixture, 8 parts of triisopropanolamine cyclic borate, 4 parts of polyvinyl pyrrolidone, 6 parts of water glass, 6 parts of pentaerythritol, 4 parts of melamine, 12 parts of ammonium polyphosphate, and 75 parts of water.

[0036] (iv) placing the modified sepiolite zeolite mixture, pentaerythritol, melamine and ammonium polyphosphate in water, and subjecting the mixture to ultrasonic treatment at an ultrasonic frequency of 100 Hz for 2 hours to obtain a slurry;

[0037] (V) Add triisopropanolamine cyclic borate, polyvinyl pyrrolidone and water glass to the slurry obtained in step (IV), and perform ultrasonic treatment at an ultrasonic frequency of 40 Hz for 1 hour to obtain a product.

[0038] Example 2

[0039] 1. Preparation of modified sepiolite:

[0040] (1) placing sepiolite in a 5 mol / L hydrochloric acid aqueous solution at a solid-liquid ratio of 1 g:20 mL, treating at 60° C. for 18 hours, washing with distilled water and drying to obtain acid-treated sepiolite;

[0041] (2) placing the acid-treated sepiolite, titanium dioxide and silicon dioxide in an ethanol aqueous solution with a volume fraction of 80% ethanol in a weight ratio of 8:1:2, and ultrasonically treating the solution for 2 hours at an ultrasonic frequency of 100 Hz to fully mix and uniformly form a slurry;

[0042] (3) Add an ethanol aqueous solution of γ-methacryloxypropyltrimethoxysilane (the weight fraction of γ-methacryloxypropyltrimethoxysilane in its ethanol aqueous solution is 3%) to the obtained slurry at a volume ratio of 1:3, then adjust the pH to 5, stir and incubate at 60° C. for 5 hours, then filter and wash with anhydrous ethanol, and then vacuum dry to obtain the product.

[0043] (II) Preparation of modified sepiolite zeolite mixture:

[0044] The modified sepiolite and zeolite obtained in step (i) were mixed in a weight ratio of 5:1, and then sintered in a muffle furnace at 600° C. for 2 hours, and then ball-milled to obtain a particle size distribution of 80-120 μm.

[0045] (III) Preparation of coating raw materials:

[0046] Prepare the following raw materials by weight: 18 parts of a modified sepiolite zeolite mixture, 15 parts of triisopropanolamine cyclic borate, 5 parts of polyvinyl pyrrolidone, 5 parts of water glass, 8 parts of pentaerythritol, 3 parts of melamine, 15 parts of ammonium polyphosphate, and 80 parts of water.

[0047] (iv) placing the modified sepiolite zeolite mixture, pentaerythritol, melamine and ammonium polyphosphate in water, and subjecting the mixture to ultrasonic treatment at an ultrasonic frequency of 100 Hz for 2 hours to obtain a slurry;

[0048] (V) Add triisopropanolamine cyclic borate, polyvinyl pyrrolidone and water glass to the slurry obtained in step (IV), and perform ultrasonic treatment at an ultrasonic frequency of 40 Hz for 1 hour to obtain a product.

[0049] Example 3

[0050] 1. Preparation of modified sepiolite:

[0051] (1) placing sepiolite in a 5 mol / L hydrochloric acid aqueous solution at a solid-liquid ratio of 1 g:20 mL, treating at 60° C. for 18 hours, washing with distilled water and drying to obtain acid-treated sepiolite;

[0052] (2) placing the acid-treated sepiolite, titanium dioxide and silicon dioxide in an ethanol aqueous solution with a volume fraction of 80% ethanol in a weight ratio of 8:1:2, and ultrasonically treating the solution for 2 hours at an ultrasonic frequency of 100 Hz to fully mix and uniformly form a slurry;

[0053] (3) Add an ethanol aqueous solution of γ-methacryloxypropyltrimethoxysilane (the weight fraction of γ-methacryloxypropyltrimethoxysilane in its ethanol aqueous solution is 3%) to the obtained slurry at a volume ratio of 1:3, then adjust the pH to 5, stir and incubate at 60° C. for 5 hours, then filter and wash with anhydrous ethanol, and then vacuum dry to obtain the product.

[0054] (II) Preparation of modified sepiolite zeolite mixture:

[0055] The modified sepiolite and zeolite obtained in step (i) were mixed in a weight ratio of 5:1, and then sintered in a muffle furnace at 600° C. for 2 hours, and then ball-milled to obtain a particle size distribution of 80-120 μm.

[0056] (III) Preparation of coating raw materials:

[0057] Prepare the following raw materials by weight: 10 parts of a modified sepiolite zeolite mixture, 5 parts of triisopropanolamine cyclic borate, 3 parts of polyvinyl pyrrolidone, 8 parts of water glass, 5 parts of pentaerythritol, 5 parts of melamine, 10 parts of ammonium polyphosphate, and 60 parts of water.

[0058] (iv) placing the modified sepiolite zeolite mixture, pentaerythritol, melamine and ammonium polyphosphate in water, and subjecting the mixture to ultrasonic treatment at an ultrasonic frequency of 100 Hz for 2 hours to obtain a slurry;

[0059] (V) Add triisopropanolamine cyclic borate, polyvinyl pyrrolidone and water glass to the slurry obtained in step (IV), and perform ultrasonic treatment at an ultrasonic frequency of 40 Hz for 1 hour to obtain a product.

[0060] Comparative Example 1

[0061] Except that titanium dioxide was not added when preparing the modified sepiolite, the rest was consistent with Example 1.

[0062] Comparative Example 2

[0063] Except that silicon dioxide was not added when preparing the modified sepiolite, the rest was consistent with Example 1.

[0064] Comparative Example 3

[0065] Except that the modified sepiolite-zeolite mixture is replaced by modified sepiolite, the rest is the same as Example 1.

[0066] Comparative Example 4

[0067] Except that the weight proportion of the modified sepiolite zeolite mixture is adjusted to 5 parts, the rest is the same as that of Example 1.

[0068] Comparative Example 5

[0069] Except that polyvinyl pyrrolidone was not added, the rest was the same as in Example 1.

[0070] Experimental Example 1

[0071] The fire retardant coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were uniformly coated on the surface of clean steel plates without an oxide layer, and the coating thickness was 15 mm. The fire resistance limit was examined according to GA / T714-2007 "Rapid Heating Fire Resistance Test Method for Fire Protection Materials for Components"; the water resistance, smoke corrosion resistance, and heat exposure resistance were examined according to GB14907-2018 "Fire Retardant Coatings for Steel Structures". The experimental results are shown in Tables 1 and 2.

[0072]

[0073] Note: The water resistance time in Table 2 means that there is no delamination, blistering or falling off during this time and the thermal insulation efficiency reduction is ≤35%; the heat exposure resistance time in Table 2 means that there is no delamination, falling off, hollowing or cracking during this time and the thermal insulation efficiency reduction is ≤35%; the smoke corrosion resistance times in Table 2 means that there is no blistering, obvious deterioration or softening during this test and the thermal insulation efficiency reduction is ≤35%.

[0074] As shown in Table 2, the refractory coating obtained by the present invention has excellent water resistance. After more than 42 days of treatment, there is no delamination, bubbling, or shedding phenomenon, and the thermal insulation efficiency attenuation is ≤35%. Its water resistance time far exceeds the 24 hours specified in GB14907-2018 (hereinafter referred to as the standard). In addition, the heat exposure time of the refractory coating obtained by the present invention also far exceeds the 720 hours specified in the standard, reaching more than 1840 hours; on the other hand, the refractory coatings obtained in Comparative Examples 1 and 3 failed to meet the requirements of the standard in this indicator. Although Comparative Examples 2, 4, and 5 met the requirements of the standard, they were only slightly better than the requirements of the standard. Similarly, the refractory coating obtained by the present invention also has excellent smoke corrosion resistance. After more than 86 cycles of smoke corrosion treatment specified in the standard, there is still no bubbling, obvious deterioration, softening, and the thermal insulation efficiency attenuation is ≤35%; on the other hand, the refractory coatings obtained in Comparative Examples 1 to 5 either failed to meet the standard requirements or were only slightly better than the standard requirements.

[0075] In addition to far exceeding the requirements of the relevant indicators of the standards, the fire-resistant coating obtained by the present invention is also better than the existing research known to the inventor. For example, ZL201910033706.0 provides a fire-retardant coating interface agent. After using it as a fire-retardant coating for steel, the heat exposure resistance obtained is only up to 728 hours, which is far lower than the performance of the fire-retardant coating obtained in this application in this regard. For example, the graphene-modified fire-retardant coating provided by ZL 201811302481.6 has a maximum fire resistance limit of only 137 hours; at the same time, the aerogel non-expanding steel structure fire-retardant coating provided by ZL 202211105230.5 has a maximum fire resistance limit of only 270 hours. Although it also has excellent water resistance, its water resistance is not as good as the fire-resistant coating obtained by the present invention.

[0076] Experimental Example 2

[0077] In addition to conventional tests, the inventors also investigated the high-temperature heat insulation performance of the fire-resistant coating obtained by the present invention. The fire-retardant coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were uniformly coated on the surface of clean steel plates without an oxide layer, with a coating thickness of 15 mm. After drying, the steel plate surface coated with the fire-retardant coating was sprayed with a spray gun with an external flame temperature of 1300°C for 3 minutes (room temperature was 26°C), and the temperature of the back side of the steel (the other side relative to the coating) after 3 minutes was recorded, and whether cracks visible to the naked eye appeared on the coating surface. The results are shown in Table 3.

[0078]

[0079] Note: Basic cracking in Table 3 means that the area containing cracks accounts for more than 70% of the coating area of ​​the specimen; partial cracking means that the area containing cracks accounts for 30% to 70% of the coating area of ​​the specimen.

[0080] As shown in Table 3, the coating obtained by the present invention has excellent heat insulation effect under short-term high temperature. As far as the inventors know, in the 15mm steel structure fire retardant coating, on the basis of achieving the fire resistance limit, heat exposure resistance, water resistance and smoke corrosion resistance in Experimental Example 1, there is no report on obtaining such high temperature heat insulation performance.

Claims

1. A non-expanding fire retardant coating for steel structures, characterized in that: The fire retardant coating comprises the following components by weight: 10 to 18 parts of a modified sepiolite zeolite mixture, 5 to 15 parts of triisopropanolamine cyclic borate, 3 to 5 parts of polyvinyl pyrrolidone, 5 to 8 parts of water glass, 5 to 8 parts of pentaerythritol, 3 to 5 parts of melamine, 10 to 15 parts of ammonium polyphosphate, and 60 to 80 parts of water; The modified sepiolite-zeolite mixture is prepared by mixing modified sepiolite and zeolite in a weight ratio of 5:1 and sintering at high temperature; The preparation method of the modified sepiolite comprises: (1) soaking sepiolite in hydrochloric acid to obtain acid-treated sepiolite; (2) placing the acid-treated sepiolite, titanium dioxide and silicon dioxide in an ethanol aqueous solution in a weight ratio of 8:1:2, and fully mixing them under ultrasonic conditions to form a slurry; (3) adding the obtained slurry to an ethanol aqueous solution of γ-methacryloxypropyltrimethoxysilane, then adjusting the pH to 5, stirring and incubating at 60° C. for 5 hours, then filtering and washing with anhydrous ethanol, and then vacuum drying to obtain the modified sepiolite.

2. A non-expanding fire retardant coating for steel structures according to claim 1, characterized in that: The preparation method of the acid-treated sepiolite is as follows: according to a solid-liquid ratio of 1 g:20 mL, the sepiolite is placed in a 5 mol / L hydrochloric acid aqueous solution, treated at 60° C. for 18 hours, and then washed with distilled water and dried to obtain the sepiolite.

3. A non-expanding fire retardant coating for steel structures according to claim 2, characterized in that: In step (2) of the method for preparing modified sepiolite, the ultrasonic conditions are: ultrasonic frequency is 100 Hz, and the treatment time is 2 hours.

4. A non-expanding fire retardant coating for steel structures according to claim 3, characterized in that: In step (2) of the method for preparing modified sepiolite, the volume fraction of the ethanol aqueous solution is 80%, and the weight fraction of the γ-methacryloxypropyltrimethoxysilane after being dissolved in the ethanol aqueous solution is 3%.

5. A non-expanding fire retardant coating for steel structures according to claim 4, characterized in that: When preparing the modified sepiolite-zeolite mixture, the modified sepiolite and zeolite are mixed in a weight ratio of 5:1, and then sintered in a muffle furnace at 600° C. for 2 hours.

6. A non-expanding fire retardant coating for steel structures according to claim 1 or 5, characterized in that: The fire retardant coating comprises the following components by weight: 15 parts of a modified sepiolite zeolite mixture, 8 parts of triisopropanolamine cyclic borate, 4 parts of polyvinyl pyrrolidone, 6 parts of water glass, 6 parts of pentaerythritol, 4 parts of melamine, 12 parts of ammonium polyphosphate, and 75 parts of water.

7. A non-expanding fire retardant coating for steel structures according to claim 6, characterized in that: The modified sepiolite zeolite mixture is also ball-milled to have a particle size distribution of 80-120 μm.

8. A method for preparing a non-expanding fire retardant coating for steel structures, characterized in that: The preparation method comprises the following steps: (1) Prepare raw materials according to the weight proportions of each raw material in a non-expanding fire retardant coating for steel structures according to any one of claims 1 to 7; (2) dispersing the modified sepiolite zeolite mixture, pentaerythritol, melamine, and ammonium polyphosphate in water to prepare a slurry; (3) adding triisopropanolamine cyclic borate, polyvinyl pyrrolidone and water glass to the obtained slurry for dispersion treatment to obtain the fire retardant coating.

9. The preparation method according to claim 8, characterized in that: In step (2), the dispersion is carried out under ultrasonic treatment, the ultrasonic frequency is 100 Hz, and the treatment time is 2 hours.

10. The preparation method according to claim 8 or 9, characterized in that: In step (3), the dispersion treatment is carried out under ultrasonic treatment, the ultrasonic frequency is 40 Hz, and the treatment time is 1 hour.

Citation Information

Patent Citations

  • A graphene-modified fire-retardant coating and its preparation method

    CN109627867B

  • A fire-retardant coating interface agent and its preparation method

    CN109735179B

  • An aerogel non-intumescent fireproof coating for steel structures and its preparation method

    CN115612332B

  • High-performance water-based anticorrosion paint and preparation method thereof

    CN102134410A

  • Water-resistant fireproof coating

    CN105176247A